THE CONTRIBUTION OF BPRS BHAKTI SUMEKAR PRATAMA GILI GENTING BRANCH IN IMPROVING THE PERFORMANCE OF MSMEs - Kamil, Insan; Pardiman; Eka Farida (Pena Cendekia Insani, 2025)
This study aims to analyse the contribution of BPRS Bhakti Sumekar Pratama Gili Genting Branch in improving the performance of MSMEs in the islands through sharia financing and integrated business coaching. This research method uses qualitative field research through observation and interviews with BPRS employees, customers, and the local community. Data analysis techniques include data reduction, data presentation, drawing conclusions, and triangulation of data sources using Nvivo 12 Pro. The results of this study indicate that BPRS Bhakti Sumekar Pratama Gili Genting Branch contributes to improving the performance of MSMEs through two financing programmes, Mitra UMKM and Berani Mekar, as well as through guidance and mentoring. Factors influencing BPRS contributions are internal, such as human resources, product agreements, services, and location. External factors such as the absence of direct competitors, government policies, bad credit, and limited direct transportation. The contribution of BPRS to MSME players has an impact on increasing income and business management. The contribution of BPRS to local economic development through financing to MSME players has an impact on productive businesses by meeting the needs and providing employment opportunities for the local community.